2020
DOI: 10.1101/2020.09.28.20202952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of face-masks used in Uganda: a laboratory-based inquiry during the COVID-19 pandemic

Abstract: Background With shortages of face-masks continuing to be reported worldwide, critical questions like whether or not there is an adequate alternative to commercially manufactured face-masks continue to linger especially in low- and middle- income settings. This study aimed at addressing this through testing and comparing various materials and forms of face-masks for filtration efficiency, breathability, microbial cleanliness, distance-dependent fitness, and re-usability of different face-masks procured from fa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Furthermore, a synthesis of the literature on COVID-19 SOPs in Sub-Sahara Africa are in supports of the above explanation [3,13,14]. The banks and the employees therein could be very cautious to protect themselves and their families against COVID-19, this is in support of a study conducted in Uganda which reported that nearly all individuals reported having done something to protect themselves and their families from COVID-19 [6]. In addition, the banks could be complying with the COVID-19 SOPs because of the closed environmental conditions (air conditioners) for which its employees are exposed, which are generally riskier than open environments.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Furthermore, a synthesis of the literature on COVID-19 SOPs in Sub-Sahara Africa are in supports of the above explanation [3,13,14]. The banks and the employees therein could be very cautious to protect themselves and their families against COVID-19, this is in support of a study conducted in Uganda which reported that nearly all individuals reported having done something to protect themselves and their families from COVID-19 [6]. In addition, the banks could be complying with the COVID-19 SOPs because of the closed environmental conditions (air conditioners) for which its employees are exposed, which are generally riskier than open environments.…”
Section: Discussionsupporting
confidence: 53%
“…Since the research relied on observational method of data collection, there is need to conduct research on the factors associated with low level of compliance to COVID-19 SOPs among individuals in public places. Also, level of compliance in the risk groups for Covid-19 that is to say Health workers, security personals, cleaners and Boda bodas among others [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a synthesis of the literature on COVID-19 SOPs in Sub-Sahara Africa are in support of the above explanation , (Puspitasari et al, 2020). The banks and the employees therein could be very cautious to protect themselves and their families against COVID-19, this is in support of a study conducted in Uganda which reported that nearly all individuals reported having done something to protect themselves and their families from COVID-19 (Mboowa et al, 2020). In addition, the banks could be complying with the COVID-19 SOPs because of the closed environmental conditions (air conditioners) for which its employees are exposed, which are generally riskier than open environments.…”
Section: Discussionmentioning
confidence: 67%
“…The study was conducted in Iganga public places that included; gazzetted markets, public transport stations and financial banks in the district. The researcher decided to use this area because it had a high population traffic and literature synthesis on COVID-19 reveals 3 of 12 that the virus is spread fast where there is high population traffic (Mboowa et al, 2020), thus the choice of the study area.…”
Section: Study Sitementioning
confidence: 99%